Bi-Parabolic temperature variation effect on free vibration of visco–elastic parallelogram plate with linear thickness variation in one dimensions - Upasana; Dr. Vijyeta Verma (Utilitas Mathematica, 2025)
This study analyzes the vibration modes of a non-homogeneous isotropic parallelogram plate with one-dimensional thickness variation, focusing on CSCS edge conditions, where "C" and "S" denote clamped and simply supported edges, respectively.. Thermal Induced vibration of these plates has been taken as bi-parabolic temperature distributions in both directions.. The time period corresponding to the first two modes of vibration has been calculated for a parallelogram plate under CSCS boundary conditions for various values of aspect ratio, thermal constant and taper constant.